We have to find x if (x^1/3)^(logx x^2 +2)=2log3 27

(x^1/3)^(log(x) x^2 +2) = 2 log(3) 27

=> (x^1/3)^(log(x) x^2 +2) = 2*3 log(3) 3

=> (x^1/3)^(log(x) x^2 +2) = 6

=> (x^1/3)^(2 + 2) = 6

=> (x^4/3) = 6

=> x= 6^(3/4)

**The value of x is 6^(3/4)**

We have to find x if (x^1/3)^(logx x^2 +2)=2log3 27

(x^1/3)^(log(x) x^2 +2) = 2 log(3) 27

=> (x^1/3)^(log(x) x^2 +2) = 2*3 log(3) 3

=> (x^1/3)^(log(x) x^2 +2) = 6

=> (x^1/3)^(2 + 2) = 6

=> (x^4/3) = 6

=> x= 6^(3/4)

**The value of x is 6^(3/4)**